EnglishEffect Ulomoides dermestoides extract to TNF-α expression and kidney histopathology in diabetic rat model - Andre Giovanni; Hendrawan, Viski Fitri; Mahdi, Chanif (ARSHI Veterinary Letters, 2022)
Type 1 diabetes mellitus is a degenerative disease that often occurs, that is caused by impaired insulin production and damage to the cell β pancreas. This disease is characterized by increased levels of glucose in the blood, which interferes with insulin production in the body. Rattus norvegicus was used as an animal model of diabetes mellitus with streptozotocin 20 mg/kg and five experimental groups with three therapeutic doses of 2.3 mg/kg, 4.6 mg/kg, and 9.2 mg/kg. The total flavonoid equivalent contained in Ulomoides dermetoides was 1.48 g/mL. Immunohistochemistry results showed therapeutic doses of 2.3 mg/kg and 4.6 mg/kg can reduce TNF-α expression in kidney tissue, but a dose of 9.2 mg/kg had no effect when compared to the positive control. Necrosis and protein deposits were seen in the renal tubules in the four treatment groups compared with the negative control. A dose of 2.3 mg/kg was the best treatment with high TNF-α expression and can repair kidney tissues.